Sobre William B. Taylor, Landlord and Peasant in Colonial Oaxaca. Sobre Pedro Alonso O'Crouley, A Description of the Kingdom of New Spain (1774) - Florescano, Enrique (El Colegio de México, A.C., 1973)
-